Relationships of people with intellectual disabilities in Ireland - Garcia Iriarte, Edurne (My University, 2012)
This study explored the perspectives of people with learning disabilities on relationships and supports in the Republic of Ireland. A national research network consisting of 21 researchers with learning disabilities, 12 supporters, and 7 university researchers conducted the study. Researchers with learning disabilities and their supporters ran 16 focus groups with peers with learning disabilities. A total of 97 adults with learning disabilities from across the country took part in the focus groups. Findings suggest that people with learning disabilities have a diversity of experiences and views on relationships and support needed to keep them. People with learning disabilities taking part in the focus groups identified that they need more support from friends, family, and services staff to develop new relationships and keep their existing ones. This support includes both emotional and systematic changes such as accessible transport, own housing, and changed laws. The article discusses how the research team used the findings to advocate for a change in the laws concerning sexuality and learning disability in the Republic of Ireland.
PUBLISHED
Keywords: Learning (intellectual) disabilities; Research; Sexuality; Inclusive Society